2019
DOI: 10.1016/j.nicl.2019.102088
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted functional and structural connectivity within default mode network contribute to WMH-related cognitive impairment

Abstract: HighlightDisconnective DMN contribute to impaired cognition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 48 publications
1
52
1
Order By: Relevance
“…However, it should be noted that there was a significant difference both in the nocturnal systolic pressure and the diastolic pressure between OSA group and HCs group in the current study, which are common manifestations in OSA due to the interaction between nocturnal intermittent hypoxemia, hypercapnia, sleep fragmentation, neurohormonal dysregulation, and sympathetic activation (42). Recent studies demonstrated the impact of hypertension on cognitive impairment and FC alterations (43,44). The study by Li and his colleagues indicated that impaired attention and executive function existed in patients with hypertension, and furthermore, altered FC in the frontoparietal networks mediated the effects of changes of white matter on the decreased executive function in patients with hypertension (43).…”
Section: Discussion Fc Abnormality In the Hippocampal Network In Osacontrasting
confidence: 46%
See 1 more Smart Citation
“…However, it should be noted that there was a significant difference both in the nocturnal systolic pressure and the diastolic pressure between OSA group and HCs group in the current study, which are common manifestations in OSA due to the interaction between nocturnal intermittent hypoxemia, hypercapnia, sleep fragmentation, neurohormonal dysregulation, and sympathetic activation (42). Recent studies demonstrated the impact of hypertension on cognitive impairment and FC alterations (43,44). The study by Li and his colleagues indicated that impaired attention and executive function existed in patients with hypertension, and furthermore, altered FC in the frontoparietal networks mediated the effects of changes of white matter on the decreased executive function in patients with hypertension (43).…”
Section: Discussion Fc Abnormality In the Hippocampal Network In Osacontrasting
confidence: 46%
“…Recent studies demonstrated the impact of hypertension on cognitive impairment and FC alterations (43,44). The study by Li and his colleagues indicated that impaired attention and executive function existed in patients with hypertension, and furthermore, altered FC in the frontoparietal networks mediated the effects of changes of white matter on the decreased executive function in patients with hypertension (43). Similarly, Carnevale et al also found that the altered FC network was associated with cognitive impairment and brain microstructural injury in patients with hypertension (44).…”
Section: Discussion Fc Abnormality In the Hippocampal Network In Osamentioning
confidence: 99%
“…An experienced neuropsychologist conducted all the testing. The raw scores were transformed to Z-scores for each test [30,31], which could be computed as follows:…”
Section: Neuropsychological Testingmentioning
confidence: 99%
“…The plasticity of fiber microstructure can be compensated temporarily, and we hypothesized that decompensation may occur with the further deterioration of patients' cognitive function, and this definitely needs to be confirmed by our follow-up studies in a larger sample. Next, structural damage may be accompanied by enhanced functional connectivity, which can enhance one's cognition (Chen et al, 2019b ). This of course needs further research including functional magnetic resonance.…”
Section: Discussionmentioning
confidence: 99%